The Role and Requirements of Sulphurous for Ruminant - Karto, Abdurrays Ambar (Indonesian Bulletin of Animal and Veterinary Sciences, 1999)
Sulphurous is one of the important mineral that essential for. the living organism. For the animals, sulphurous (S) has a positive correlation with the nitrogen retention. Beside that, S is one of the essential component for methionine, and the methionine could be found in all of hormonal and enzymatic compounds and also in could be detected in all of the cell of the animal . For example, to continue the reproduction activities, animals need S for synthesizing reproduction hormones, ovulation and spermatogenesis. Fortunately for ruminants, because they could yield protein as a cycle of the ruminal activities. The prerequisite of this processif the branch C-frame is available for energy resources or C-frame from microorganism protein, S and ammonia (NH3). All of the components would work in synchronizing to build the protein. S could be supply from organic and inorganic materials and would be harvested from fermented protein in the nimen. 3lme materials from plants are generally containing low S especially for legumes and oily seeds, and also depend on the S contained under land where the plant is growth. In addition, S also has a synergistic with P, Mg and Co and antagonistic with the Cu and Se. S is also as one of important component in biotin and thiamine that have a role in periver neural systemic, tract digestive, cardiovascular systemic and the thiamine it self also has a special function for beri-beri medicine. Key words : Sulphurous, requirement, role